Gilda de Mello e Souza e as artes menores - Valle, Rafael Lopes do (Universidade Federal de São Carlos, 2021)
Throughout her essays and articles, Gilda de Mello e Souza presents us with a study of what she calls as minor arts. These differ from other artistic productions for being ordinary, applied and closely linked to society. The minor arts are part of a poor aesthetic, so-called by the philosopher, whose object of investigation is the everyday phenomena, futile and without forums of grandeur. Another characteristic that is attributed to the minor arts is that of the well-done, because they require an attachment to minuteness and detail, characteristics that Gilda de Mello e Souza associates with a feminine vision. Therefore, the minor arts are works that are neither historical nor European, in addition to those produced by women. Although they are despised objects, it is seen, throughout our author's work, that the designation given to minor arts should not be taken in a pejorative sense, but viewed by their dignity.
Gilda de Mello e Souza and the minor arts
Keywords: Gilda de Mello e Souza; Filosofia da arte; Artes menores; Arte moderna; Philosophy of art; Minor arts; Modern art; CIENCIAS HUMANAS::FILOSOFIA::FILOSOFIA BRASILEIRA